Amphotericin B induced pancytopenia - Esha Vaish; Kamlesh K Gupta; Shahnawaz A Ansari; Kaushal K Singh (Journal of Family Medicine and Primary Care, 2022)
Amphotericin B (AMB) has been the irreplaceable drug of choice for countless fungal and protozoal infections. One of the lesser-known adverse effects of AMB is Pancytopenia - very rare with very few cases reported - most commonly observed following prolonged administration. We report the case of a patient suffering from visceral leishmaniasis, who developed worsening pancytopenia four to five days after being administered a single bolus dose of Liposomal Amphotericin B (L-AMB). The diagnosis was clinical and management involved supportive care, and granulocyte-macrophage colony-stimulating factor (GM-CSF). AMB is an effective drug, but is also associated with numerous side effects. Physicians are well-versed with the more frequently seen adverse drug reactions and their management. However, pancytopenia, being a rare adverse reaction to AMB, is less known and can be easily overlooked. This case report aims to ensure that the physicians must be aware of such possibilities in the first place to make swift diagnoses and management. The condition itself is seemingly self-limiting, although GM-CSF may be needed in refractory cases. It's true that few previous case reports have indicated pancytopenia in association with prolonged AMB exposure, but we believe certain conditions may predispose a patient to a more acute presentation - as seen in our case.